2010
DOI: 10.1074/jbc.m110.110015
|View full text |Cite
|
Sign up to set email alerts
|

A Plasma Membrane Wound Proteome

Abstract: Cells in mechanically active tissues undergo constant plasma membrane damage that must be repaired to allow survival. To identify wound-associated proteins, a cell-impermeant, thiolreactive biotinylation reagent was used to label and subsequently isolate intracellular proteins that become exposed on the surface of cultured cells after plasma membrane damage induced by scraping from substratum or crushing with glass beads. Scrape-damaged cells survived injury and were capable of forming viable colonies. Protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 47 publications
(53 reference statements)
0
21
0
Order By: Relevance
“…On the basis of a variety of considerations, we think it likely that most of the membranous compartments near the wound site would be likely to fuse with the plasma membrane upon exposure to the millimolar level of calcium in the extracellular medium (Bement et al 2007). Consistent with this expectation, proteomic analysis of plasma membrane wounds has revealed several components of the endoplasmic reticulum (Mellgren 2010) in membrane patches.…”
Section: Single-cell Wound Healingmentioning
confidence: 62%
“…On the basis of a variety of considerations, we think it likely that most of the membranous compartments near the wound site would be likely to fuse with the plasma membrane upon exposure to the millimolar level of calcium in the extracellular medium (Bement et al 2007). Consistent with this expectation, proteomic analysis of plasma membrane wounds has revealed several components of the endoplasmic reticulum (Mellgren 2010) in membrane patches.…”
Section: Single-cell Wound Healingmentioning
confidence: 62%
“…Interestingly, in the same study, cell-surface PDIA6 was found to associate with integrins, suggesting that PDIA6 may contribute to platelet activation by affecting the configuration of disulfide bonds of several integrins. These intriguing effects were extended further when it was shown that PDIA6 was one of several other ER proteins that relocated to the cell surface upon plasma membrane wounding [50]. Cell-surface PDIA6 has also been shown to promote tumor immune evasion through the shedding of tumor associated ligands [51].…”
Section: Discussionmentioning
confidence: 99%
“…In fibroblasts, calpain mediates the rapid fragmentation of talin and vimentin after wounding, as a first step towards the removal of damaged cytoskeleton [8]. Calpain has also been shown to rapidly cleave caldesmon, a calmodulin dependent actin-linked protein involved in actin filament stabilization and actomyosin contraction, suggesting an alternative mechanism facilitating the rapid disassembly and clearance of the local cytoskeleton at the wound site [9]. …”
Section: Single Cell Wound Repairmentioning
confidence: 99%